2012
DOI: 10.1093/ejcts/ezr286
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and neurodevelopmental outcome at 1 year of age comparing hybrid and Norwood procedures

Abstract: Mortality at 1 year of age is comparable between patients undergoing hybrid and Norwood procedures. Early neurodevelopmental outcome is significantly impaired in patients with both HLHS and other UVH defects. Multicentre randomized studies are needed to determine the long-term neurodevelopmental outcome of children treated with the hybrid procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 19 publications
1
59
0
2
Order By: Relevance
“…The question remains if the Hybrid technique will yield similar results. Only one study to date has reported neurodevelopmental outcomes in this cohort of HLHS patients following Hybrid Stage I palliation compared to the traditional Norwood procedure [16]. Results showed no significant difference in 1 year mortality.…”
Section: Discussionmentioning
confidence: 84%
“…The question remains if the Hybrid technique will yield similar results. Only one study to date has reported neurodevelopmental outcomes in this cohort of HLHS patients following Hybrid Stage I palliation compared to the traditional Norwood procedure [16]. Results showed no significant difference in 1 year mortality.…”
Section: Discussionmentioning
confidence: 84%
“…Data comparing neurodevelopmental outcomes, one of the main potential theoretical advantages of the hybrid procedure, are only just starting to emerge. Knirsch et al analysed neuromotor scores at 3 and 12 months in 31 patients (Hybrid 13, NW 18) [1]. Neurodevelopmental outcome was significantly lower overall in patients with hypoplastic left heart syndrome compared with normal, with no significant difference between Norwood 1 and hybrid groups.…”
Section: Catheter Interventional Track Overviewmentioning
confidence: 99%
“…Neonatal cardiopulmonary bypass can cause brain injury, which can result in severely impaired motor and cognitive neurodevelopmental outcomes, although notable advances and innovations have been made in cardiopulmonary bypass, surgical techniques, and instruments [3,4]. Moreover, patients with severe coronary heart disease (CHD) have significantly impaired early neurodevelopmental outcomes, although the mortality rate after a hybrid procedure is similar to that after the Norwood procedure [5].…”
Section: Introductionmentioning
confidence: 99%